Short Communication: The composition of mangrove species in coastal area of Banggai District, Central Sulawesi, Indonesia - RAMLI UTINA; ABUBAKAR SIDIK KATILI; NURAIN LAPOLO; TALHA DANGKUA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Utina R, Katili AS, Lapolo N, Dangkua T. 2019. Short Communication: The composition of mangrove species in coastal area of Banggai District, Central Sulawesi, Indonesia. Biodiversitas 20: 840-846. The mangrove ecosystem possesses unique ecological functions. This research is one part of the activities to prepare reports on mangrove condition in Banggai District, Central Sulawesi Province, Indonesia. The objectives of this study were to explore the composition of mangrove species and mangrove zoning in coastal area of Banggai. The data were collected by survey method spread within 16 spots, with a total area of 7,387 hectares. The data were analyzed with descriptive qualitative methods. The results showed that there were 32 families of mangrove plants in Banggai, classified into 53 species, consisting of 25 true mangrove species and 28 associated mangrove species. An endangered species of mangrove was found, i.e., Scyphiphora hydrophyllacea. This endangered species was found only in Tingki-tingki Village and Uwedikan Village (Balean and Potean Island) of Banggai. The pattern of mangrove zoning within the research site follows the pattern of mangrove zoning commonly found all over Indonesia. The Rhizophoraceae family (Bruguiera gymnorhiza, Rhizophora mucronata, Rhizophora apiculata, Rhizophora stylosa, Rhizophora lamarchii and Ceriops tagal) was found more often than the other families in study site. It means that the Rhizophoraceae family had wide distribution area within site.